Pengembangan Media Komik Edukatif Interaktif Berbasis Canva untuk Pembelajaran IPAS di Sekolah Dasar - Rinadevi; Abna Hidayati; Yalvema Miaz; Elfia Sukma (Postgraduate, University of Mataram, 2025)
The integration of technology into elementary education is essential for creating engaging and meaningful learning experiences. This study aims to develop an interactive educational comic based on Canva as an innovative learning medium to enhance students’ motivation and learning outcomes in Natural and Social Sciences (IPAS). The objective is to produce a learning medium that is valid, practical, and effective for use in elementary schools. This research adopts a Research and Development approach using the 4D model comprising Define, Design, Develop, and Disseminate stages. Data were collected through expert validation questionnaires, classroom observations, and learning achievement tests, and analyzed using descriptive quantitative techniques to determine the validity, practicality, and effectiveness of the product. The results show that the Canva-based educational comic obtained a validity score of 98.2 percent indicating a highly valid category, a practicality score of 94.7 percent indicating a highly practical category, and an N-Gain score of 0.74 indicating high effectiveness in improving learning outcomes. These findings demonstrate that the developed media can significantly enhance students’ conceptual understanding and learning engagement in IPAS. In conclusion, the Canva-based interactive comic is a feasible and beneficial learning medium for elementary education and contributes to the development of digital learning resources that align with the Merdeka Curriculum. Future research is recommended to apply this media across different grade levels and subjects while integrating more dynamic interactive features to enrich the learning experience.